Evaluation of introduced plum varieties under extreme climatic conditions - Surányi, D. (International Journal of Horticultural Science, 2019)
In the gene bank variety collection, 15 plum varieties were examined based on morphogenetic and pomological traits. Most cultivars of self-fertilizing or pollinating partners were well-cultivated. In addition to Queston, Stanley, Valor and Verity, towards 11 new cultivars have been experienced in this paper. From the observations, it seems that the growth and plantation of Valor, Presenta, Topfive and Bellamira can increase. However, the Top Sugar and Valor fruit sizes are best suited to market requirements. The role of Stanley may be reduced, but there is no reason to replace it. However, the questions of local varieties of domestic origin fall into a different category, and raw materials for quality products are difficult to replace with other varieties.